The Evaluatıon Of Cranıofacıal Morphology Changes İn Young Adults: A Longıtudınal Study - Ayça Arman Akgül; T. Ufuk Toygar; Hakan Gögen (Galenos Yayinevi, 2000)
The aim of this study is to evaluate the changes of the craniofacial morphology and dental arches, which take place in young adults. The study material consisted of lateral cephalometric films obtained at the natural head position and dental casts of 12 girls and 12 boys, totally 24 individuals. The mean age at the beginning of the observation period was 22.01±0.56 years, and 31.83±0.66 years at the end of the observation period. The observation period was approximately 10 years (9.82±0.47). Postural, craniofacial and dentoalveolar changes were evaluated using 37 parameters. The statistical significance of the changes in the measurements during the observation period was determined by paired t-test. The relationships between the differences of the model measurements and the cephalometric parameters at the beginning and end of the observation period were evaluated by correlation analysis. Our findings indicated that from the cranial measurements, only the N-S measurement increased (p < 0.01), Cd-Gn and Go-Me measurements of the mandible changed at p < 0.0l and p < 0.05 levels respectively during the observation period. From the maxillo-mandibular measurements, ANB and ANSPNS.GoMe angles were found different at p < 0.05 level. All the dental cast measurements except maxillary arch length discrepancy and intercanine width showed significant decrease. According to the correlation analysis between the dental cast measurements and craniofacial measurements only few correlations were found. As a result, in the post-adolesence period -although being small- changes were found in all of the craniofacial parameters and these changes were more significant in the dental arch level during the 10 years observation period. These findings express the importance of the duration and type of the retention treatment of the patients being treated or finished in the post-adolescence period.